Property crime and violent crime in Detroit: spatial association with built environment before and during COVID-19 - Tokey, Ahmad Ilderim (Bulletin of Geography. Socio-economic Series, 2023)
This study expands the literature by finding the associations of land use (LU) and road-related Built Environment (BE) with property and violent crime in Detroit from 2019 to 2021. It builds two spatial models with a wide range of built environment elements and sociodemographic information. Findings indicate that the retail and office LU proportion, bus stop density, and density of roads of less than 40 miles per hour are positively linked with crime rates. Conversely, block groups' median income, population density, and tenure length are inversely associated with crime rates. Single-family houses experienced more violent crime in low-income neighborhoods and less in highincome neighborhoods. Bus stop densities in downtown were more positively associated with violent crime in 2020–2021 than in the pre-pandemic time. This study advances understanding related to the BE–crime relationship during the pandemic, sheds new light on street-related BE, and leaves essential evidence for local policymakers in Detroit.